Chiral cyclopalladium (II) complexes promoted asymmetric synthesis of optically active functionalized bidentate phosphine ligands - Tang, Lulu (2008)
In this thesis, a systematic review of chiral cyclopalladated complexes is described in Chapter 1. This chapter reviews the classification of chiral palladium(II) complexes, and synthetic method of chiral palladium(II) complexes. In addition, their major applications in catalytic asymmetric synthesis including C-C bond formation reaction and C-Heteroatom bond formation reaction, together with their application in asymmetric stoichiometric reactions including asymmetric insertion reaction, Diels-Alder reaction, and hydroamination reaction are discussed. In Chapter 2, the selective oxidation of a C-prochiral tridentate phosphine ligand with hydrogen peroxide, elemental sulfur or elemental selenium in the presence of an optically active palladium(II) template are thoroughly investigated. Two synthetic methods are tried out to obtain an equilibrium mixture of up to four diastereomeric precursors. The insertion of P(O)-H moiety in P(O)Ph2H into the activated C-C double bond in 1,1-bis(diphenylphosphino)ethene was conducted in order to verify the presence of a four-membered ring intermediate in the corresponding equilibrium mixture. The liberated enantiomerically pure triphosphine mono-oxide and triphosphine mono-sulfide ligands were recoordinated to a homochiral palladium(II) template. Thus four diastereomeric phosphine-palladium(II) complexes generated after selective oxidation reaction were identified. In Chapter 3, resolution of a racemic triphosphine ligand containing a C-prochiral and P-stereogenic centres by metal complexation followed by selective oxidation performed by hydrogen peroxide is demonstrated. Theoretically, up to eight diastereomeric products could be produced, as three stereogenic centres appeared in each diastereomeric complex together with the relative arrangement of the four asymmetric donors at palladium(II) centre. Only five of them were predominately obtained, and the major isomer could be isolated into its optically pure form in a high yield. Accordingly the liberated enantiomerically pure triphosphine mono-oxide ligands containing both C- and P-stereogenic centres in one molecule was recoordinated to S- or R-form chiral palladium(II) template. Thus four diastereomeric phosphine-palladium(II) complexes generated in the mixture of five diastereomeric products after selective oxidation reaction were identified. Apart from secondary phosphine ligands, a N-H moiety in benzyl amine was attempted to be added into the activated double bond in 1,1-bis(diphenylphosphino)ethylene. A P-N hetero five-membered ring was formed at the palladium(II) centre, however the isolated product was confirmed to be an racemic dichloro palladium(II) complex, so was the liberated P-N hetero ligand. In Chapter 4, selective oxidation of a P-prochiral tridentate phosphine ligand bis(2-diphenylphosphinoethyl)phenylphosphine by using hydrogen peroxide, elemental sulfur or elemental selenium to generate a P-chiral tridentate phosphine ligand is thoroughly investigated. The major phosphine-palladium(II) diastereomeric product in each selective oxidation was able to be isolated into its enantiomerically active form. Only the chiral ligand with mono-oxide functional group was stable after removal from palladium(II) stabilization. The rest two chiral ligands containing mono-sulfide and mono-selenide functional groups were found racemized after removal from palladium(II) stabilization. Therefore only the four diastereomeric phosphine-palladium(II) complexes generated after selective oxidation reaction performed by hydrogen peroxide were identified. In Chapter 5, addition of diphenylphosphine to cis- or trans-diphenyl(styryl)phosphine in the presence of a chiral palladium(II) template is demonstrated. Attempts to isolate either phosphine-palladium(II) product in its enantiomerically active form were unsuccessful. The separated neutral dichloro palladium(II) complex was found to be a racemic one, so was the liberated ligand. Besides, addition of diphenylphosphine into an activated triple bond in dimethyl acetylene dicarboxylate in the presence of a chiral palladium(II) template was also demonstrated in Chapter 5. Two diastereomeric products were formed, although theoretically up to four diastereomers could be generated as three stereogenic centres appeared in each diastereomeric complex. Attempts to isolated either of them in its enantiomerically active form were unsuccessful. Therefore acid treatment was performed in order to remove the chiral auxiliary at the palladium(II) template. A mixture of isomeric neutral dichloro palladium(II) complexes enriched in one optical form was obtained. The enriched isomer could be separated into its enantiomerically pure form and the corresponding chiral diphosphine ligand having C2 symmetry was liberated from palladium(II) stabilization. Accordingly the two diastereomeric phosphine-palladium(II) complexes generated after hydrophosphination reaction were identified.